2016
DOI: 10.1111/jphp.12674
|View full text |Cite
|
Sign up to set email alerts
|

Germacrone inhibits adipogenesis and stimulates lipolysis via the AMP-activated protein kinase signalling pathway in 3T3-L1 preadipocytes

Abstract: Our results suggest that GM may be a potent bioactive anti-adipogenic and lipolytic constituent via the regulation of adipogenesis, lipolysis and the AMPKα pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…It is reported that AMPK activators cannot increase the expression of p21 together with compound C-upregulated preadipocytes expansion 43. Activation of AMPK contributed to germacrone-reduced adipogenesis 44. It seems that the activation of AMPK in obesity was differentially regulated in response to different treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that AMPK activators cannot increase the expression of p21 together with compound C-upregulated preadipocytes expansion 43. Activation of AMPK contributed to germacrone-reduced adipogenesis 44. It seems that the activation of AMPK in obesity was differentially regulated in response to different treatments.…”
Section: Discussionmentioning
confidence: 99%
“…2.4 | Gene screening, plasmid construction, and small interfering RNA (siRNA) transfection Except for Rac family small GTPase 2 (RAC2), the other 19 genes had been reported the relationship with adipogenesis in human, such as brain-derived neurotrophic factor (BDNF) (Bernhard et al, 2013), IGF1 (Hu et al, 2015), insulin receptor substrate 2 (IRS2) (Miki et al, 2001), leptin receptor (LEPR) (Yue, Zhou, Shimada, Zhao, & Morrison, 2016), lipase E (LIPE) (Holm, Osterlund, Laurell, & Contreras, 2000), Rap guanine nucleotide exchange factor 3 (RAPGEF3) (Bos, 2006;Tang & Lane, 2012), and suppressor of cytokine signaling 3 (SOCS3) (Liu et al, 2010), human and mice, such as fatty acid binding protein 4 (FABP4) (Garin-Shkolnik, Rudich, Hotamisligil, & Rubinstein, 2014) and peroxisome proliferator activated receptor gamma (PPARG) coactivator 1 alpha (PPARGC1A) (Mazzucotelli et al, 2008), mice, such as acetyl-CoA carboxylase beta (ACACB) (Guo & Choung, 2017), acyl-CoA synthetase long-chain family member 1 (ACSL1) (Mukherjee & Yun, 2012), coagulation factor II thrombin receptor (F2R) (Kajimoto, Takayanagi, Sasaki, Akita, & Harashima, 2012), fatty acid synthase (FASN) (Rosolen et al, 2016), leptin (LEP) (Rhee, Sung, Jung, & Cheon, 2008), phosphodiesterase 3B (PDE3B) (Guirguis et al, 2013), perilipin 1 (PLIN1) (Lyu et al, 2015), stearoyl-CoA desaturase (SCD) (Ralston & Mutch, 2015;Christianson, Nicoloro, Straubhaar, & Czech, 2008), and signal transducer and activator of transcription 3 (STAT3) (Yuan et al, 2017), and chicken, such as phosphoenolpyruvate carboxykinase 1 (PCK1) (Eubank, Duplus, Williams, Forest, & Beale, 2001). To validate the function of the 20 identified candidate genes responsible for adipogenesis from hMSCs, three genes, such as F2R encoding coagulation factor II thrombin receptor, PCK1 encoding, and RAC2 encoding, were randomly selected as the candidates for RNA interference assays.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…GER, which has previously shown activity toward lipid metabolism, has been described as an antiadipogenic and lipolytic constituent via the regulation of adipogenesis, lipolysis and the AMP-activated protein kinase α (AMPKα) pathway in 3T3-L1 preadipocytes [ 27 ]. In high fat diet mice, attenuation of hyperlipidemia and improved lipid metabolism were suggested by suppressed fatty acid synthesis and uptake by inhibiting SREBP-1 and 2 signaling activation along with improved lipid metabolism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of targets common for both sesquiterpenes led us to further focus on cholesterol metabolism and the major regulating enzyme of mevalonate pathway 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR). Since GER has been described to attenuate hyperlipidemia in high-fat diet obese mice [ 26 ] as well as to inhibit adipogenesis and stimulate lipolysis in 3T3-L1 preadipocytes [ 27 ], the changes in the expression of major genes responsible for de novo lipogenesis, triglyceride synthesis, and lipid sequestration in dHepaRG cells after ATL and GER treatment were evaluated.…”
Section: Introductionmentioning
confidence: 99%